HEALTHCARE FIELD MANAGEMENT AND ACTIVITY MULTIFACTOR MODEL BASED DEVELOPMENT PROSPECTS - Mirzaev Abdullajon Topilovich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
the article examines the management activities of the health sector in theoretical and practical terms. In the course of the study, a model was developed based on the connections of the number of patients recorded with the diagnosis made for the first time in relation to 100,000 inhabitants in the Republic of Uzbekistan and the indicators of the factor influencing its change. When using this structured trend Model, determining the volume of resources (exogenous factors) entering the industry taking into account the effect that each unit receives from an additional unit of incoming resource is based on the possibilities of optimal resource efficiency.